Nedubroviidae, a new family of Mecoptera: the first Paleozoic long-proboscid scorpionflies - Bashkuev, Alexei S. (Zootaxa, 2011)
Nedubroviidae fam. nov. consists of Nedubrovia gen. nov., with Nedubrovia shcherbakovi sp. nov. as the type species, N. deformis sp. nov., and N. mostovskii comb. nov., originally described in Mesopanorpodes. The second genus of Nedubroviidae is Paranedubrovia gen. nov., with Paranedubrovia novokshonovi sp. nov. as the type species, and including P. minutissima sp. nov. Of these five species, all originate from the Late Permian of European Russia except for the Early Triassic N. mostovskii. The wing venation of these species indicates membership in the long-proboscid mecopteran clade Aneuretopsychina. The body structure of one species, N. shcherbakovi, includes a long proboscis consistent with fluid feeding on contemporaneous plants.